2017
DOI: 10.1002/jor.23641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and pathology on shear wave speed of the human rotator cuff

Abstract: Rotator cuff tears are common and often repaired surgically, but post-operative repair tissue healing, and shoulder function can be unpredictable. Tear chronicity is believed to influence clinical outcomes, but conventional clinical approaches for assessing tear chronicity are subjective. Shear wave elastography (SWE) is a promising technique for assessing soft tissue via estimates of shear wave speed (SWS), but this technique has not been used extensively on the rotator cuff. Specifically, the effects of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 49 publications
3
67
2
Order By: Relevance
“…7 Additionally, age-associated high elasticities of the supraspinatus and Achilles tendon were also reported. 6,23 The men : women ratio in these studies ranged from 1:1 to 8:1. Therefore, from the results of previous reports and the present study, age-related changes in elasticities were observed regardless of sex, and they are common changes in men and women.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…7 Additionally, age-associated high elasticities of the supraspinatus and Achilles tendon were also reported. 6,23 The men : women ratio in these studies ranged from 1:1 to 8:1. Therefore, from the results of previous reports and the present study, age-related changes in elasticities were observed regardless of sex, and they are common changes in men and women.…”
Section: Discussionmentioning
confidence: 87%
“…Eby et al reported that the elasticity of the biceps brachii of individuals aged >60 years increased with age . Additionally, age‐associated high elasticities of the supraspinatus and Achilles tendon were also reported . The men : women ratio in these studies ranged from 1:1 to 8:1.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In case of small supraspinatus tears, several Authors 53,59,60 reported the torn tendons to be softer (mean strain index 0.75 ± 0.08) compared with the contralateral healthy shoulder (1.01 ± 0.07) (Figs. [3][4][5].…”
Section: Shouldermentioning
confidence: 99%